Morphological control for high proton conduction in robust Co3O4-diethylmethylamine (metal-organic framework) membrane - Yadav G.; Jha P.K.; Jha P.A.; Singh P.K.; Choudhary S.R.; Singh P. (My University, 2025)
Metal-organic framework (MOF) based proton conductors are synthesized by the Avrami model (time-temperature modalities). Our objective here is to obtain a material with high proton conductivity in anhydrous conditions, improved catalytic behaviour and morphology control of conductivity, band gap and catalysis. For this purpose, we try to understand the role of morphology on mass transportation using computational fluid dynamics and the experimental realisation using the synthesis of MOF membranes with high protonic conductivity. In order to alter the morphology, the membranes are synthesized from protic ionic liquid (dimethyl ethyl amine H2PO4) and metal ion (Co3O4) at different temperatures and duration. A high protonic conductivity of 0.0286 S cm−1 with a high transference number >0.99 is observed in anhydrous conditions with the change in morphology. Furthermore, catalyst properties along with high activity (Tafel slope = 39 mV decade−1) with the alteration in morphology are also investigated in detail and observed adsorption governed conduction. This adsorption governed conduction is verified using computational fluid dynamics simulations with the alteration in morphology. This study suggests that morphology not only plays a pivotal role in obtaining a robust proton exchange membrane, it also improves the catalytic functionality and stability of the membrane. © 2023 The Royal Society of Chemistry